2018
DOI: 10.1021/acs.jafc.8b03231
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestibility of Nanoporous Wheat Starch Aerogels

Abstract: This study reports the in vitro digestibility of starch aerogels for the first time. The relative crystallinities of the wheat starch aerogels (WSAs) produced at gelatinization temperatures of 120 °C (WSA-120C), 130 °C (WSA-130C), and 120 °C with the addition of sodium metaphosphate (STMP) (WSA-STMP) and xerogel were similar. However, WSA-120C showed the highest amylose-lipid complex content. The addition of STMP created some cross-linked starch with a phosphorus content of 0.023%. Resistant starch (RS) conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 44 publications
5
24
0
Order By: Relevance
“…CSA with STMP had a better 3D network structure and higher degree of crosslinking than CSA with other crosslinking agents, which was consistent with the study by Ubeyitogullari et al. [ 16 ]…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…CSA with STMP had a better 3D network structure and higher degree of crosslinking than CSA with other crosslinking agents, which was consistent with the study by Ubeyitogullari et al. [ 16 ]…”
Section: Resultssupporting
confidence: 91%
“…Compared with the control, CSA with crosslinking agents showed an increase in the BET surface area, which was consistent with the result by Perez–Cantu et al. [ 26 ] Crosslinking agents would decrease the pore volume, [ 16 ] which could explain the phenomenon of decreased BET surface of CSX added with SHMP, but increased the number of micropores to increase the BET surface area. Thus, crosslinking agents could be used to produce more homogenous and stable network structure, which was consistent with the results by Ubeyitogullari et al.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The starch-based aerogels with excellent biocompatibility and biodegradability have been widely used in drug delivery, due to a wide range of sources and the porous structure. [83][84][85] Pawar et al 86 reported a starchbased drug delivery material which was developed by converting native starch from hydrogel to aerogel. This starch-based aerogels improved the dissolution and oral bioavailability of a poorly water-soluble antifungal drug of Itraconazole.…”
Section: Aerogel-based Biomaterials For Drug Deliverymentioning
confidence: 99%
“…The starch type (empty NSA vs pregelatinized starch) was the sole different ingredient in those non-fat granola bar control formulations. The physical properties of the NSA and pregelatinized starch could differ in terms of crystallinity, porosity, surface area and density (Ubeyitogullari, Brahma, Rose, & Ciftci, 2018;Ubeyitogullari & Ciftci, 2016a) which might affect the water solubility/water absorption and consequently alter the hardness. A higher lipid content in the granola bar formulations could interfere with the interaction between the ingredients such as starch and water which might result in a decrease in hardness.…”
Section: Granola Bar Formulationmentioning
confidence: 99%